2019
DOI: 10.1093/asj/sjz074
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Implants in Breast Reconstruction: A Comparison of Outcomes and Aesthetic Results Compared to Smooth Round Silicone Implants

Abstract: Background Direct comparison studies of outcomes and aesthetic satisfaction of anatomic implants compared to other implants are scarce in the literature. Objectives The objective of this study was to compare outcomes and aesthetic satisfaction of patients who underwent breast reconstruction with anatomic implants vs other implants (smooth round silicone). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…There is currently no evidence that a difference in aesthetic outcome exists between textured anatomic implants and smooth round implants in breast reconstruction. 33 , 34 In this regard, and since a variety of cohesivity levels are widely available with smooth devices, it may be prudent for plastic surgeons to utilize implants with smooth shells, which can produce excellent aesthetic results while eliminating the potential risk for BIA-ALCL.…”
Section: Avoiding and Managing Most-dangerous Complicationsmentioning
confidence: 99%
“…There is currently no evidence that a difference in aesthetic outcome exists between textured anatomic implants and smooth round implants in breast reconstruction. 33 , 34 In this regard, and since a variety of cohesivity levels are widely available with smooth devices, it may be prudent for plastic surgeons to utilize implants with smooth shells, which can produce excellent aesthetic results while eliminating the potential risk for BIA-ALCL.…”
Section: Avoiding and Managing Most-dangerous Complicationsmentioning
confidence: 99%
“…Comparing pros and cons of both shapes, the risk of malrotation is one of the main drawbacks of anatomical implants, which is around 5%, especially after subglandular placement. [1][2][3][4][5] The development of BIA-ALCL…”
Section: Introductionmentioning
confidence: 99%
“…There are few longitudinal BREAST-Q studies in the surgery research literature; a 2016 systematic review noted that only 29% of PRO studies using BREAST-Q were prospective, while 71% were cross-sectional [ 21 ]. BREAST-Q completion rates have been reported as low as 27% [ 22 , 23 ], demonstrating the need for increased investment and investigation into strategies for improving patient participation in this important health metric for both clinical care and research. One strategy evaluated in areas outside of breast reconstruction is the use of electronic PROM administration; however, studies have shown low sustainability with decreasing patient compliance when electronic PROM capture methods were not coupled with additional reminders or manual administration by research or clinical staff.…”
Section: Introductionmentioning
confidence: 99%